LECTURER'S STRATEGIES IN TEACHING SPEAKING DURING COVID-19 PANDEMIC - Rusmanhadi Takbir; Ratna Dewi; Farisha Andi Baso (Indonesian Journal of Psycholinguistics, 2023)
This research aimed to reveal what were the strategies used by the lecturers in teaching speaking during the covid-19 pandemic. This research used qualitative research. The subject of this research was two speaking lecturers who taught at Universitas Muhammadiyah Makassar. The instruments of this research were observation and interview. The technique of data analysis used the miles and Huberman model; data reduction, data display, and conclusion drawing/verification. The result of this research revealed six kinds of strategies that were applied by the two subjects. They were; (1) questioning strategy, (2) games strategy, (3) multimedia presentation strategy, (4) reward and punishment strategy, (5) a time token strategy, and (6) drilling strategy.